Cherenkov emission provides detailed picture of non-thermal electron dynamics in the presence of magnetic islands. (12th November 2015) - Causa, F.; Buratti, P.; Esposito, B.; Pucella, G.; Giovannozzi, E.; Jakubowski, L.; Malinowski, K.; Rabinski, M.; Sadowski, M.J.; Zebrowski, J.
Abstract: Results from a Cherenkov probe recently installed in FTU are presented on non-thermal electron losses. A range of scenarios are investigated to prove the versatility of the diagnostics by correlation with several other diagnostics, including electron cyclotron emission (ECE), neutron and gamma ray detectors, Mirnov coils and soft x-ray cameras. The data analysed provide useful insights into the dynamics of runaway electron (RE) losses in the presence of magnetic islands, demonstrating the distinct and broad potential of this relatively new diagnostic system. The analysis focuses on the sensitivity of the Cherenkov probe to RE losses in connection with magnetohydrodynamic activity and, generally, with magnetic perturbations and reconnection events. In those cases, the Cherenkov probe signals show that the RE expulsion mechanisms are due to the magnetic perturbation of a magnetic island and its amplitude fluctuations. Importantly, the microsecond resolution of the Cherenkov diagnostics reveals an internal structure of the signal peaks, permitting, for the first time with non-magnetic diagnostics, the detection of high frequency signals linked to perturbations of the magnetic island width, known as beta-induced Alfvèn eigenmodes.